Psychological Features of Teacher’s Professional Competence - Mudryk, Alla (Psychological Prospects Journal, 2014)
The paper outlines the main theoretical approaches to the study of professional competence, its features. The  professional competence of teachers is viewed as based on the architectonics of the structural content of the professional competence related to through structural and functional components that are defined by functionally professional competencies and professionally important qualities seen as key elements of communicative-characterological features. The results of the empirical study of psychological characteristics of future teachers’ professional competence show a set of psychological factors that contribute to the formation of it. A special attention is paid to the structural and functional components of the future teachers’ professional competence (intellectual, motivational, communicative, emotionally regulational, general culture, special) and to the factors which define the components. The conclusions contain the characteristics of professional competence and level of its acquirement by student teacher, point to the prospects for further research aimed at finding the methods how to become a skillful teacher, along with the applied aspects of constructing harmonious environment for his professionalization.